Screen Printing as a Scalable and Low-Cost Approach for Rigid and Flexible Thin-Film Transistors Using Separated Carbon Nanotubes - Cao, Xuan; Chen, Haitian; Gu, Xiaofei; Liu, Bilu; Wang, Wenli; Cao, Yu; Wu, Fanqi; Zhou, Chongwu (ACS nano, 2014)
Semiconducting single-wall carbon nanotubes are very promising materials in printed electronics due to their excellent mechanical and electrical property, outstanding printability, and great potential for flexible electronics. Nonetheless, developing scalable and low-cost approaches for manufacturing fully printed high-performance single-wall carbon nanotube thin-film transistors remains a major challenge. Here we report that screen printing, which is a simple, scalable, and cost-effective technique, can be used to produce both rigid and flexible thin-film transistors using separated single-wall carbon nanotubes. Our fully printed top-gated nanotube thin-film transistors on rigid and flexible substrates exhibit decent performance, with mobility up to 7.67 cm2 V–1 s–1, on/off ratio of 104 ∼ 105, minimal hysteresis, and low operation voltage (<10 V). In addition, outstanding mechanical flexibility of printed nanotube thin-film transistors (bent with radius of curvature down to 3 mm) and driving capability for organic light-emitting diode have been demonstrated. Given the high performance of the fully screen-printed single-wall carbon nanotube thin-film transistors, we believe screen printing stands as a low-cost, scalable, and reliable approach to manufacture high-performance nanotube thin-film transistors for application in display electronics. Moreover, this technique may be used to fabricate thin-film transistors based on other materials for large-area flexible macroelectronics, and low-cost display electronics.